Protecting Intellectually Disabled Child Victims Of Sexual Violence In Court Proceedings - Nadhine Fakhira Putri Ravanti; Sarah Yessie Hana Monica (Jurist-Diction, 2025)
Intellectually disabled individuals have long faced social exclusion, making them vulnerable to violence which was left unreported. Childrens with intellectual disabilities are twice as likely to have a higher risk of exploitation. The situation raises alarms on the need to accommodate their special needs in ensuring equal treatments in court proceedings. This paper examines the challenges faced by the victims in the justice system using normative research methods to analyze legal cases by reviewing and analyzing various aspects of written laws and doctrines to resolve the continuous violation. The results provide that when the cases did make their way to the court proceedings, just 9% of the victims were accompanied by a translator, whilst 18% did not get any assistance, and the 82% rest of the victims did not have any experts as their representation. When the cases were reported and reached the court, they were often treated with discrimination. Tackling that problem the current regulation precisely Law Number 8 of 2016 on Persons with Disabilities need to better ensure the protection of intellectually disabled children meanwhile the court needs to provide assistance such as interpreters and health care workers to assist the victims. The urgency of this research is to promote equality and ensure the intellectually disabled children as victims will receive their well-deserved justice.